BPR KB Financial Performance Improvement: A simpler approach - Raharjo, Adi Prasetio; Koesrindartoto, Deddy P (The Indonesian Journal of Business Administration, 2012)
The bank in research is in a complicated situation where it is considered healthy by BI but under performing if being compared to other bank. Trough Du-Pont and common-size analysis, it is obtained that the bank in question is underleveraged and has lots of non-performing loan. And one way to increase the leverage is to analyze its funding product and provide a marketing plan accordingly. And creating an implementation plan and action plan to tackle the problem. Keywords: Du-Pont, BPR, Common-Size, Business Model Generation